Orientation and dynamics of Cu2+ based DNA labels from force field parameterized MD elucidates the relationship between EPR distance constraints and DNA backbone distances. Issue 46 (7th November 2020) - Ghosh, Shreya; Casto, Joshua; Bogetti, Xiaowei; Arora, Charu; Wang, Junmei; Saxena, Sunil
Abstract : MD simulations highlight how EPR distance constraints from Cu 2+ -DPA labels can be interpreted in terms of DNA structure. Abstract : Pulsed electron paramagnetic resonance (EPR) based distance measurements using the recently developed Cu 2+ -DPA label present a promising strategy for measuring DNA backbone distance constraints. Herein we develop force field parameters for Cu 2+ -DPA in order to understand the features of this label at an atomic level. We perform molecular dynamics (MD) simulations using the force field parameters of Cu 2+ -DPA on four different DNA duplexes. The distance between the Cu 2+ centers, extracted from the 2 μs MD trajectories, agrees well with the experimental distance for all the duplexes. Further analyses of the trajectory provide insight into the orientation of the Cu 2+ -DPA inside the duplex that leads to such agreement with experiments. The MD results also illustrate the ability of the Cu 2+ -DPA to report on the DNA backbone distance constraints. Furthermore, measurement of fluctuations of individual residues showed that the flexibility of Cu 2+ -DPA in a DNA depends on the position of the label in the duplex, and a 2 μs MD simulation is not sufficient to fully capture the experimental distribution in some cases. Finally, the MD trajectories were utilized to understand the key aspects of the double electron electron resonance (DEER) results. The lack of orientational selectivity effects of the Cu 2+ -DPA at Q-band frequency is rationalized in terms of fluctuations in the Cu 2+ coordination environment and rotameric fluctuations of the label linker. Overall, a combination of EPR and MD simulations based on the Cu 2+ -DPA labelling strategy can contribute towards understanding changes in DNA backbone conformations during protein–DNA interactions.